Subjective Happiness and Compassion Are Enough to Increase Teachers’ Work Engagement? - De Stasio, Simona; Fiorilli, Caterina; Benevene, Paula; Boldrini, Francesca; Ragni, Benedetta; Pepe, Alessandro; Maldonado Briegas, Juan José (Frontiers in Psychology, 2019)
The present quantitative multi-trait cross-sectional study aims to gain a better understanding of the network of relationship between subjective happiness, compassion, levels of work engagement, and proactive strategies (self- and co-regulation) in a sample of teachers. Participants were 187 full-time in-service teachers (89% female; age M = 48.5; SD = 7.88) from Rome, Italy. We hypothesized that subjective happiness and compassion of early childhood teachers would be related with work engagement in such a way that subjective happiness would promote the engagement of teachers. In a similar fashion, we theorized that subjective happiness would be positively related to self- and co-regulation strategies and that proactive strategies would be in turn associated to work engagement. As expected, the results revealed that subjective happiness and compassion showed effects on work engagement and that this association among constructs was mediated by the role of proactive strategies (β = 0.22, p < 0.001; β = 0.37, p < 0.001, respectively). Proactive strategies also have a significant direct effect on work engagement (β = 0.56, p < 0.001). The study’s findings suggest the importance of investing in the quality of the working environment.